Problems with Peer Response of Writing-as-a-Process Approach in an EFL Writing Classroom - Utami Widiati (Universitas Negeri Malang, 2016)
This paper is the result of reflection on personal experience in teaching writing using the process approach at the Department of English, State University of Malang, Indonesia. It firstly describes the current practice of teaching writing courses at the Department. Following this, ESL writing literature is explored to show how process approaches have been accepted in ESL composition. Then, the paper discusses some problems in teaching writing at the Department using the approach, referring more specifically to peer response activities. Finally, it offers a pedagogic proposal in the form of training strategies for peer response through classroom action research.